Justicia paracambi, a new Brazilian species of Acanthaceae - Braz, Denise Monte (Phytotaxa, 2015)
Justicia paracambi is described as a new, so far strictly endemic species to the state of Rio de Janeiro, which occurs in an area of natural forest in the Parque Natural Municipal do Curió, in the city of Paracambi. It differs from other Justicia L. species by the presence of dense glandular and non-glandular trichomes on the rachis, on the bracts and bracteoles and on the calyx, the terminal, lax panicle of spikes with decussate branches and flowers, the calyx 5-lobed, the white to greenish corolla and by the anthers with the lower thecae with a remarkable basal appendage. According to its restricted area of occurrence and the approximate number of individuals, it is considered critically endangered. The new species is described and illustrated and comments on its occurrence, phenology, taxonomy and diagnostic characters are provided.